2010
DOI: 10.1590/s0101-20612010005000016
|View full text |Cite
|
Sign up to set email alerts
|

Características físico-químicas e microbiológicas de morango minimamente processado

Abstract: A produção brasileira de morangos no ano de 2007 foi estimada em aproximadamente 100 mil toneladas, com uma área ocupada de 3.500 ha (ANTUNES et al., 2007), uma produção pequena quando comparada a de outros países como os EUA, que alcança 998,8 mil toneladas (USDA, 2005). Entretanto, a produção nacional de morangos se expande a cada ano, com predominância do cultivo em pequenas propriedades rurais. Por se tratar de exploração que agrega mão de obra familiar, possui grande importância econômica e social, caract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
2
6
0
3
Order By: Relevance
“…For the treatments with 5% hydrogen peroxide and 40 mg/mL peracetic acid with or without ultrasound, the average brightness value was higher than 28.45. Ponce, Bastiani, Minim, and Vanetti (2010) evaluated the effects of different sanitizers on strawberries and found that they resulted in higher L* values compared with a control treatment (32.37) and 200 mg/mL sodium dichloroisocyanurate (30.95). These authors also observed that sanitizing with 10% hydrogen peroxide reduced the L* value, resulting in a loss of brightness in the product and compromising its appearance.…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…For the treatments with 5% hydrogen peroxide and 40 mg/mL peracetic acid with or without ultrasound, the average brightness value was higher than 28.45. Ponce, Bastiani, Minim, and Vanetti (2010) evaluated the effects of different sanitizers on strawberries and found that they resulted in higher L* values compared with a control treatment (32.37) and 200 mg/mL sodium dichloroisocyanurate (30.95). These authors also observed that sanitizing with 10% hydrogen peroxide reduced the L* value, resulting in a loss of brightness in the product and compromising its appearance.…”
Section: Tablementioning
confidence: 99%
“…These authors also observed that sanitizing with 10% hydrogen peroxide reduced the L* value, resulting in a loss of brightness in the product and compromising its appearance. Maintaining the color of strawberries during storage is known to be important because the darkening of fruit affects its visual appearance, which consequently affects consumer acceptance (Ponce et al, 2010). Therefore, it is important to choose a sanitizing agent that has a low impact on product color because alterations in color can increase during the storage period.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…é de aproximadamente 4,52 milhões de toneladas (FAO, 2014). A produção brasileira estimada de morangos é de cerca de 100 mil toneladas (Ponce et al, 2010;Randin et al, 2011), sendo de cerca de 6.500 toneladas no Distrito Federal (EMATER-DF, 2014).…”
Section: Introductionunclassified
“…é de aproximadamente 4,52 milhões de toneladas (FAO, 2014). A produção brasileira estimada em 2007 foi de cerca de 100 mil toneladas, com expansão significativa a cada ano (PONCE et al, 2010;RANDIN et al, 2011).A produção do Distrito Federal é de cerca de 6.500 toneladas (EMATER-DF, 2014 WU et al, 2006).…”
Section: Introductionunclassified